Fármacos de repropósito para combatir la quimiorresistencia en el cáncer ovárico epitelial - Garrido P., Maritza; Romero O., Carmen (Revista Hospital Clínico Universidad de Chile, 2023)
Epithelial ovarian cancer (EOC) is one of the most lethal gynecological cancers both in Chile and worldwide. Treatment in advanced stages is cytoreductive surgery followed by chemotherapy, based on platinum and taxanes. Unfortunately, resistance to chemotherapy is a frequent phenomenon in patients with EOC, worsening their prognosis. Therefore, the study of new drugs or complementary therapies to existing ones is essential to benefit EOC patients. Drug repurposing, or the use of old drugs that are commonly used for other purposes, may be key in the development of new therapies for EOC. This strategy, unlike de novo drug development, can be much cheaper, safer, and faster to implement. In this context, widely used drugs such as metformin and nonsteroidal anti-inflammatory drugs (NSAIDs) have shown promising antitumor effects in the context of cancer, including in different EOC models. In this work, we review the current evidence related to the antitumor effects of metformin and NSAIDs in tumor cells, with an emphasis on ovarian cancer cells and their projections for use in the context of EOC.